The Association Between Notching of the Right Ventricular Outflow Tract Flow Velocity Doppler Envelope and Impaired Right Ventricular Function After Acute High-Altitude Exposure - Yuan, Fangzhengyuan; Liu, Chuan; Yu, Shiyong; Bian, Shizhu; Yang, Jie; Ding, Xiaohan; Zhang, Jihang; Tan, Hu; Ke, Jingbin; Yang, Yuanqi; He, Chunyan; Zhang, Chen; et al. (Frontiers in Physiology, 2021)
Introduction Pulmonary artery pressure (PAP) is increased and right ventricular (RV) function is well preserved in healthy subjects upon exposure to high altitude (HA). An increase in PAP may trigger notching of the right ventricular outflow tract Doppler flow velocity envelope (RVOT notch), which is associated with impaired RV function in patients with pulmonary hypertension. However, whether HA exposure can induce RVOT notch formation and the subsequent impact on cardiac function in healthy subjects remains unclear. Methods A total of 99 subjects (69 males and 30 females) with a median age of 25 years were enrolled in this study; they traveled from 500 to 4100 m by bus over a 2-day period. All subjects underwent a comprehensive physiological and echocardiographic examination 1 day before ascension at low altitude and 15 ± 3 h after arrival at HA. The RVOT notch was determined by the presence of a notched shape in the RVOT Doppler flow velocity envelope. The systolic PAP (SPAP) was calculated as Bernoulli equation SPAP = 4 × (maximum tricuspid regurgitation velocity)2+5 and mean PAP (mPAP) = 0.61 × SPAP+2. Cardiac output was calculated as stroke volume × heart rate. Pulmonary capillary wedge pressure (PCWP) was calculated as 1.9+1.24 × mitral E/e’. Pulmonary vascular resistance (PVR) was calculated as (mPAP-PCWP)/CO. Results After HA exposure, 20 (20.2%) subjects had an RVOT notch [notch (+)], and 79 (79.8%) subjects did not have an RVOT notch [notch (−)]. In the multivariate logistic regression analysis, the SPAP, right ventricular global longitude strain (RV GLS), and tricuspid E/A were independently associated with the RVOT notch. The SPAP, mPAP, PVR, standard deviations of the times to peak systolic strain in the four mid-basal RV segments (RVSD4), peak velocity of the isovolumic contraction period (ICV), and the peak systolic velocity (s’) at the mitral/tricuspid annulus were increased in all subjects. Conversely, the pulse oxygen saturation (SpO2), RV GLS, and tricuspid annulus plane systolic excursion (TAPSE)/SPAP were decreased. However, the increases of SPAP, mPAP, PVR, and RVSD4 and the decreases of SpO2, RV GLS, and TAPSE/SPAP were more pronounced in the notch (+) group than in the notch (−) group. Additionally, increased tricuspid ICV and mitral/tricuspid s’ were found only in the notch (−) group. Conclusion HA exposure-induced RVOT notch formation is associated with impaired RV function, including no increase in the tricuspid ICV or s’, reduction of RV deformation, deterioration in RV-pulmonary artery coupling, and RV intraventricular synchrony.